2009
DOI: 10.1111/j.1525-139x.2009.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Damage from Extracorporeal Circulation in Hemodialysis

Abstract: Blood damage is an unavoidable side effect of extracorporeal circulation. The effects of blood damage on patients' hematocrit and erythropoietin requirement as well as other potential side effects have not been studied for uneventful treatments. Comparing long nocturnal dialysis with regular 4-hour, three times per week dialysis allows for the conclusion that the influence of blood damage caused by extracorporeal circulation is small compared with biochemical effects. Acute hemolysis is one of the few remainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 67 publications
2
64
0
1
Order By: Relevance
“…However, our finding in the studied patients was that increased dialysis dose (Kt/V) is associated with higher ERI. This may be explained as a delayed hemolysis or severe changes of the erythrocyte morphology occurred after prolonged extracorporeal circulation [49]. In agreement with our study, Lopez-Gomez et al [40] reported positive association of spKt/V and ERI but failed to find a statistical significance.…”
Section: Individual Response Variations To Erythropoietin Stimulatingsupporting
confidence: 79%
“…However, our finding in the studied patients was that increased dialysis dose (Kt/V) is associated with higher ERI. This may be explained as a delayed hemolysis or severe changes of the erythrocyte morphology occurred after prolonged extracorporeal circulation [49]. In agreement with our study, Lopez-Gomez et al [40] reported positive association of spKt/V and ERI but failed to find a statistical significance.…”
Section: Individual Response Variations To Erythropoietin Stimulatingsupporting
confidence: 79%
“…• Extrinsic class: Increased mechanical stress due to kinks in the extracorporeal circulation line that can motivate macroscopic lysis of RBCs 8,9 is not relevant in our case. Notes: Dependence of r or with (A) pre-hD Ur; (B) pre-hD cr, (C) pre-hD ca; and (D) pre-hD P, comparison was between all different pairs: the two subgroups of hD patients, of low and high uremic marker concentration, and the group of healthy donors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the contribution of the roller pump or even minor mechanical stress due to the shear forces and biochemical activation due to the imperfect biocompatibility of the extracorporeal materials that unavoidably occur during dialysis cannot be neglected since these can damage RBCs. [8][9][10][11] Furthermore, a number of studies have reported that both the lipid and protein compositional profile of the RBC membrane is drastically modified during dialysis. [12][13][14][15] It is plausible to assume that these compositional modifications of the RBC membrane that are motivated by the extrinsic mechanisms [12][13][14][15] could somehow influence the membrane structure and ultimately influence the RBC lifespan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface roughness and the chemistry of the surface have major roles in hemolysis, and they may even govern capillary flow, especially at shear stress below the critical limit of ~150Pa [13]. Several hemolysis experiments conducted by researchers and investigators that all had similar tension for lysis, including but not limited to: Blachshear and Anderson (33 dyne/cm), Rand (28.6 dyne/cm) and Zydney (25.6dyne/cm) [1].…”
Section: Analysis and Methodsmentioning
confidence: 99%